2013
DOI: 10.1186/1477-7827-11-69
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation induces defective methylation in line-1 retrotransposon elements in blastocyst

Abstract: BackgroundSeries of epigenetic events happen during preimplantation development. Therefore assistant reproduction techniques (ART) have the potential to disrupt epigenetic regulation during embryo development. The purpose of this study was to investigate whether defects in methylation patterns in blastocyst due to superovulation originate from abnormal expression of Dnmts.MethodsLow- (6 IU) and high- (10 IU) dosage of PMSG was used to stimulate the female mice. The metaphase II(MII) oocytes, zygotes and blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
(58 reference statements)
2
24
3
Order By: Relevance
“…On the day of triggering, the median peak E 2 level was 4389 (2779-6307.5) pg/ml and the mean progesterone level 1.46 AE 1.71 ng/ml. The median oocyte number was 13 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The number of oocytes was significantly associated Supporting Information Tables S2 and S5), the E 2 level as a continuous variable was negatively associated with both the z-score and the birthweight of the newborns (adjusted P-value 0.009 and 0.01, respectively).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the day of triggering, the median peak E 2 level was 4389 (2779-6307.5) pg/ml and the mean progesterone level 1.46 AE 1.71 ng/ml. The median oocyte number was 13 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The number of oocytes was significantly associated Supporting Information Tables S2 and S5), the E 2 level as a continuous variable was negatively associated with both the z-score and the birthweight of the newborns (adjusted P-value 0.009 and 0.01, respectively).…”
Section: Resultsmentioning
confidence: 98%
“…Superovulation might be a source of developing epigenetic disorders in embryos derived from ART . It may partially explain the mechanism by which COS affected birthweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, superovulation leads to delayed in vitro blastocyst hatching, decreased in vivo blastocyst formation, lower implantation rates, more resorption sites and 40% fetal development retardation compared with naturally ovulating females (Van der Auwera and D'Hooghe 2001). Superovulation also disrupts the methylation status or expression levels of certain genes, such as H19 (Fauque et al 2007;Fortier et al 2008), PEG1 (Sato et al 2007), Snrpn (Fortier et al 2008), insulin-like growth factor 2 (Igf2) (Fortier et al 2008) and long interspersed nuclear element 1 (Line1) (Liang et al 2013), in human or mouse oocytes, embryos or placentas. All studies in this field are summarised in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Data from animal models supports the notion that 'over-riding' of the natural hormonal cycle is in itself associated with molecular changes to the oocyte which may impact on development of the embryo and pregnancy. A mouse study established that the superovulation process altered the epigenetic marks in oocytes with disrupted H19 expression and loss of methylation in several maternally imprinted genes in a dose-dependent manner [54]. Further, studies on both mice and cows have demonstrated changes to the epigenetic marks in the oocytes as well as fundamental changes in the epigenetic machinery of the oocyte obtained from superovulation [55].…”
Section: Ovarian Hyperstimulationmentioning
confidence: 98%